Fatores preditivos de mortalidade em pacientes pediátricos com lesão renal aguda associada com sepse - Riyuzo, Marcia C. [UNESP] (2017)
Objective To evaluate the prognosis factors of children with sepsis and acute kidney injury. Methods This was a retrospective study of children with sepsis and acute kidney injury that were admitted to the pediatric intensive care unit (PICU) of a tertiary hospital. A multivariate analysis was performed to compare risk factors for mortality. Results Seventy-seven children (47 males) were retrospectively studied, median age of 4 months. Mean length of hospital stay was 7.33 ± 0.16 days, 68.9% of patients received mechanical ventilation, 25.9% had oligo-anuria, and peritoneal dialysis was performed in 42.8%. The pRIFLE criteria were: injury (5.2%) and failure (94.8%), and the staging system criteria were: stage 1 (14.3%), stage 2 (29.9%), and stage 3 (55.8%). The mortality rate was 33.7%. In the multivariate analysis, the risk factors for mortality were PICU length of stay (OR = 0.615, SE = 0.1377, 95% CI = 0.469–0.805, p = 0.0004); invasive mechanical ventilation (OR = 14.599, SE = 1.1178, 95% CI = 1.673–133.7564, p = 0.0155); need for dialysis (OR = 9.714, SE = 0.8088, 95% CI = 1.990–47.410, p = 0.0049), and hypoalbuminemia (OR = 10.484, SE = 1.1147, 95% CI = 1.179–93.200, p = 0.035). Conclusions The risk factors for mortality in children with acute kidney injury were associated with sepsis severity.